2019
DOI: 10.1002/celc.201900784
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Selectivity between Oxygen and Chlorine towards Chlorine during the Anodic Chlorine Evolution Reaction on a Dimensionally Stable Anode

Abstract: The selectivity of the chlorine evolution reaction over the oxygen evolution reaction during the electrolysis of aqueous NaCl is, despite being very high, still insufficient to prevent expensive separation of the formed Cl2 and O2 by means of liquefaction. We hypothesize that, by decreasing the local activity of H2O near the anode surface by substantially increasing the ionic strength of the electrolyte, the oxygen evolution reaction would be suppressed, leading concomitantly to a higher selectivity of Cl2 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
(40 reference statements)
1
34
0
Order By: Relevance
“…It needs to be stressed that the volcano concept, as used in this study, is generally limited in its outreach: it allows assessing activity trends, but relies on several assumptions, for instance constant activities. Recently, it has been reported that local activities of H 2 O and Cl À and local pH are important factors that govern the CER vs. OER selectivity: [12] these quantities allow tuning CER selectivity, but are not captured by the simplified volcano method.…”
Section: Implications Of the Results On The Cer Vs Oer Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…It needs to be stressed that the volcano concept, as used in this study, is generally limited in its outreach: it allows assessing activity trends, but relies on several assumptions, for instance constant activities. Recently, it has been reported that local activities of H 2 O and Cl À and local pH are important factors that govern the CER vs. OER selectivity: [12] these quantities allow tuning CER selectivity, but are not captured by the simplified volcano method.…”
Section: Implications Of the Results On The Cer Vs Oer Selectivitymentioning
confidence: 99%
“…Regrettably, the oxygen evolution reaction (OER) constitutes a detrimental anodic side reaction under CER conditions . Even though conventionally applied dimensionally stable anodes (DSAs) reveal CER selectivity of about 97–99 %, the gaseous products Cl 2 and O 2 need to be separated from each other, corresponding to a significant fraction of the overall process costs . Therefore, the development of an electrode material that is as stable as DSAs under the harsh anodic reaction conditions, but reveals higher CER selectivity than DSAs, is an ultimate dream of chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…The electrolytes were prepared by diluting 70% HClO 4 and by adding 99% NaCl in 18.2 MΩ cm Millipore water. For experiments under different NaCl concentrations, NaClO 4 •H 2 O was added into the electrolyte to compensate the total ionic strength 23 . The pH values of the acidic electrolytes were adjusted to 0.90 ± 0.05 by adding a few drops of 70% HClO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…However, computational and experimental works revealed that MMO catalysts are also highly active for the OER, exhibiting a scaling relationship between the CER and OER 13,[17][18][19][20] . This relationship suggests that two reactions are catalysed on a similar active site of the MMOs or form a common surface intermediate species [20][21][22][23][24] . The oxidative water activation and concomitant surface oxidation on MMOs [25][26][27] are, therefore, unavoidable, leading to a decrease in active site density for the CER 25 .…”
mentioning
confidence: 97%
“…Chlorine is an essential chemical for modern society. For example, pure chlorine gas is used in a wide range of industrial manufacturing techniques, such as disinfection [24] and polymer production [25]. The dissociation of dissolved chlorine in aqueous solution forms hypochlorite (ClO − ), which is a key component in disinfectants, bleaches, deodorisers, oxidising agents, and water treatment formulations.…”
Section: Supplementary Informationmentioning
confidence: 99%